Persistence of the Efficacy of Zoster Vaccine in the Shingles Prevention Study and the Short-Term Persistence Substudy - Schmader, K. E.; Oxman, M. N.; Levin, M. J.; Johnson, G.; Zhang, J. H.; Betts, R.; Morrison, V. A.; Gelb, L.; Guatelli, J. C.; Harbecke, R.; Pachucki, C.; Keay, S.; et al. (Clinical infectious diseases, 2012)
Background. The Shingles Prevention Study (SPS; Department of Veterans Affairs Cooperative Study 403) demonstrated that zoster vaccine was efficacious through 4 years after vaccination. The Short-Term Persistence Substudy (STPS) was initiated after the SPS to further assess the persistence of vaccine efficacy. Methods. The STPS re-enrolled 7320 vaccine and 6950 placebo recipients from the 38 546-subject SPS population. Methods of surveillance, case determination, and follow-up were analogous to those in the SPS. Vaccine efficacy for herpes zoster (HZ) burden of illness, incidence of postherpetic neuralgia (PHN), and incidence of HZ were assessed for the STPS population, for the combined SPS and STPS populations, and for each year through year 7 after vaccination. Results. In the STPS as compared to the SPS, vaccine efficacy for HZ burden of illness decreased from 61.1% to 50.1%, vaccine efficacy for the incidence of PHN decreased from 66.5% to 60.1%, and vaccine efficacy for the incidence of HZ decreased from 51.3% to 39.6%, although the differences were not statistically significant. Analysis of vaccine efficacy in each year after vaccination for all 3 outcomes showed a decrease in vaccine efficacy after year 1, with a further decline thereafter. Vaccine efficacy was statistically significant for the incidence of HZ and the HZ burden of illness through year 5. Conclusions. Vaccine efficacy for each study outcome was lower in the STPS than in the SPS. There is evidence of the persistence of vaccine efficacy through year 5 after vaccination but, vaccine efficacy is uncertain beyond that point.